(untitled) (Academia Journal of Medicine, 2025)
Aim: To evaluate the effectiveness of 0.2% chlorhexidine and sesame oil (SO) in Oil Pulling Therapy (OPT) for patients with gingivitis. Materials and methods: 75 participants were divided at random into group A- Scaling only, B- Scaling with prescribed SO and C- Scaling with Chlorhexidine respectively. Participants were instructed regarding the use of OPT with SO and Chlorhexidine in addition to their regular dental hygiene regimen for 30 days. Results: The mean plaque and gingival index in group B and C was reduced after 1 month compared to baseline scores. Statistically significant variance showed between group A and B and group A and C respectively. OPT decreased gingivitis and plaque after a month but group B and C did not show significant variance. Conclusion: Because oil pulling is a domestic remedy that assists in avoiding gum infections in nations with restricted resources, we need to spread knowledge of it.